Pengukuran Kinerja Pemerintah Daerah Kota Mataram (Studi Kasus Pada Bagian Hukum Sekretariat Daerah Kota Mataram) - Waladina, Faras; Lestari, Baiq Anggun Hilendri; Astuti, Widia (Jurnal Riset Mahasiswa Akuntansi, 2025)
This research aims to describe the performance of the Legal Section of the Mataram City Regional Secretariat in 2024. The tool used to measure the performance of the Legal Section is the Performance Blueprint, which is a combination of a logic model and Friedman’s four-quadrant approach. The research approach is qualitative descriptive. Data collection techniques include document analysis and interviews with informants, namely Junior Legal Analyst, Assistant Expenditure Treasurer of the Legal Section, Legislative Drafting Officer, and Service Staff. The results of this study indicate that 50% of the performance produced by the Legal Section of the Mataram City Regional Secretariat in 2024 falls into quadrant 4, meaning it is oriented towards the quantity of efforts with a budget of Rp217,349,691.00. The remaining 50% of the performance of the Legal Division in 2024 is in quadrant 3, which means it is oriented towards the quantity of impact with a budget of Rp642,009,470.00. As a result, the performance of the Legal Section of the Mataram City Regional Secretariat in 2024 produces outcomes that are balanced between service orientation and community or societal orientation. This is due to the presence of coercive isomorphism in the form of regulations governing the work implementation of the Legal Section of the Mataram City Regional Secretariat and normative isomorphism in the form of education and training provided by the government to several employees of the Legal Section.